The Sharia Economic Ecosystem in Indonesia: Preliminary Study - Wibowo, Hendro (Indo Consultan Energi, 2025)
The Sharia economy has experienced rapid growth in Indonesia, accompanied by increasing public awareness of Islamic financial principles and government regulatory support. This is supported by the Sharia economic ecosystem, which covers the real sector based on Sharia principles. This study analyzes the structure, development, and challenges of building Indonesia's sustainable Sharia economic ecosystem. This research employs a qualitative method, incorporating a literature review approach based on relevant sources. The results of the study indicate that the Sharia economic ecosystem in Indonesia comprises four main pillars: the Halal Product Industry, the Sharia Financial Sector, Sharia Social Funds (including Zakat, Infaq, Shodaqoh, and Waqf), and Sharia Business and Entrepreneurship. Through the National Committee for Sharia Economics and Finance (KNEKS), the government has played a crucial role in developing a roadmap and promoting cross-sector collaboration. The implications of this study underscore the importance of strengthening regulations, enhancing public literacy, and fostering strategic collaboration among Sharia financial institutions, the halal industry, and ZISWAF institutions to create an inclusive and globally competitive ecosystem.